A New and Noteworthy Disease of Gamhar (Gmelina arborea Linn.) Due to Poria Rhizomorpha sp. nov. - Bagchee, K. (Indian Forester, 1953)
The life-history of a stem and root disease fungus attacking gamhar ( Gmelina arborea Linn.) in natural regeneration and plantations in shady, unfavourable and water-logged localities and in the clayey soil in the eastern states of India and Pakistan has been described. The important feature in the life-history of this plant is a cable-like rhizomorph which initially emerges from the tissues of the context as peg-like growth composed of thick-walled, long, septate hyphae. The rhizomorph is the principal organ of propagation. It perennates in the forests on the substratum of humus, debris, slash and soil and disseminates the disease when moisture is available. The fungus is a poroid Basidiomycetes and the name Poria rhizomorpha sp. nov. has been given to it. The Technical Description and Diagnosis of plant have also been given.